2021
DOI: 10.1038/s41598-021-97517-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a discrimination model between primary PLA2R-negative membranous nephropathy and minimal change disease confirmed by renal biopsy

Abstract: Membranous nephropathy (MN) and minimal change disease (MCD) are two common causes leading to nephrotic syndrome (NS). They have similar clinical features but different treatment strategies and prognoses. M-type phospholipase A2 receptor (PLA2R) is considered as a specific marker of membranous nephropathy. However, its sensitivity is only about 70%. Therefore, there is a lack of effective and noninvasive tools to distinguish PLA2R-negative MN and MCD patients without renal biopsy. A total 949 patients who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Another study on adult nephrotic syndrome patients showed high discrimination ability for MCD with an AUROC of 0.827 using two predictor variables 13 . In a study on a discrimination model between primary PLA2R-negative membranous nephropathy and MCD, logistic regression maintained an AUROC of 0.904 during development and 0.886 during validation 12 . While the previous studies have examined the effectiveness of predictive models in diagnosing MCD, all the models were classical statistical methods such as logistic regression.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another study on adult nephrotic syndrome patients showed high discrimination ability for MCD with an AUROC of 0.827 using two predictor variables 13 . In a study on a discrimination model between primary PLA2R-negative membranous nephropathy and MCD, logistic regression maintained an AUROC of 0.904 during development and 0.886 during validation 12 . While the previous studies have examined the effectiveness of predictive models in diagnosing MCD, all the models were classical statistical methods such as logistic regression.…”
Section: Discussionmentioning
confidence: 97%
“…The need for non-invasive diagnostic methods for MCD has been discussed, but studies using predictive models are limited 8, [11][12][13]32,33 . A study using logistic LASSO regression on 1009 adult nephrotic syndrome patients demonstrated the performance of AUROC 0.880, indicating the utility of predictive models for diagnosing MCD 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nomogram transforms the complex regression equation into a visual graph, making the results of the prediction model more readable. 33 The six variables in the nomogram are routine clinical variables that are readily available to clinicians. The decision curve showed the clinical utility of our model, suggesting that it may be beneficial for clinicians to use the nomogram to predict UC relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical prediction models have rapidly developed in renal disease, due to their scientific nature, accuracy, and simplicity. Examples of such models include those used for the distinction between MN and minimal change disease and between diabetic kidney disease and diabetes mellitus (20)(21)(22). However, MMN-related clinical models are currently lacking.…”
Section: Discussionmentioning
confidence: 99%